ISOLASI DAN IDENTIFIKASI SENYAWA METABOLIT SEKUNDER EKSTRAK ETIL ASETAT DAUN MANGKOKAN (NOTHOPANAX SCUTELLARIUM MERR) - Syafrinal Syafrinal (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
This study aims to isolate and identify secondary metabolite compound contained in the extract ethyl acetate leaf of Mangkokan (Nothopanax scutellarium Merr. The methods used for isolation were maseration and column chromatography. The isolated compound is white powder with melting point  at 281-282 ° C. Test results with Liebermann-Buchard reagents forming a green ring showed positive steroids. The analysis by UV-Vis spectroscopy showed maximum absorption at 202 nm and analysis IR spectroscopy showed wave numbers (cm-1), are: 1021.25 (C-O), 1645.71 (C=C ), 2930.85 (C-H), 3364.66 (O-H)